Treatment dependent impact of plasma-derived exosomes from head and neck cancer patients on the epithelial-to-mesenchymal transition - Hofmann, Linda; Waizenegger, Marie; Röth, Ralph; Schmitteckert, Stefanie; Engelhardt, Daphne; Schuler, Patrick J.; Laban, Simon; Hoffmann, Thomas K.; Brunner, Cornelia; Theodoraki, Marie-Nicole (Frontiers in Oncology, 2023)
Background: Epithelial to mesenchymal transition (EMT) is a key process in carcinogenesis of head and neck squamous cell carcinoma (HNSCC), contributing to tumor invasiveness, distant metastasis, and recurrence. Exosomes are known mediators and regulators of EMT. Here, we analyze the impact of exosomes that were primed by conventional therapy on EMT modulation. Methods: Plasmas of n = 22 HNSCC patients were collected before and after standard of care surgery and prior to adjuvant or primary (chemo)radiotherapy. Exosomes were isolated by size exclusion chromatography. Upon co-incubation of exosomes with HNSCC cells, the cellular EMT profile was analyzed by flow cytometry and RT-qPCR. Wound healing assays were performed to evaluate migratory potential of exosome-treated cells. Results: Reduction of total exosome protein after therapy and in vitro exosome induced EMT profiles were dependent on the type of treatment. Exosomal TFG-β and miRNA cargo were partly responsible for observed exosome induced EMT changes. Exosomes from recurrent patients induced higher tumor cell migration after therapy than exosomes from disease-free patients. Conclusions: HNSCC patients’ exosomes from timepoints before and after therapy were able to confer therapy induced EMT modulation in vitro and have the potential to monitor the EMT process. Exosome induced changes in migratory potential emerged as discriminants of therapy outcome.